The "Przemyśl Meditation" in relation to "Catena aurea" by St. Thomas Aquinas - Stelmach, Wojciech (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The purpose of this article is to identify parts of the Przemyśl Meditation (Rozmyślanie przemyskie, RP) that are potentially based on the text of Catena aurea. Another important component of the work is the analysis of the way in which these parts of the text functioned and of the purpose for which they were used in the Old Polish apocryphal work. It is first indicated for what purpose the author of RP may have made use of the text of Thomas Aquinas’ compilation. Analyses are then conducted concerning the way in which the translator worked with the source text. This is followed by an indication of the arrangement of the source in the apocryphal text. The ordering of quotations from the Church Fathers is not accidental, but corresponds to the ordering found in Catena aurea, and this may serve as confirmation of the assumption that Aquinas’ anthology was indeed one of the sources for RP. This work has not only proved the relatedness of the Old Polish apocryphal work to Aquinas’ text, but also draws attention to the need for continued research in this area.